Efektivitas Media Gambar Dinding Dalam Meningkatkan Kemampuan Menulis Teks Karangan Pada Siswa Kelas IV SD - Kusmiati Kusmiati (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The problem in the research was motivated by students' difficulties in writing essays. The research method used was classroom action research. This research was collaborative in nature based on problems that arose in the appreciation activity of studying Indonesian written essay material consisting of four steps of planning, action, action implementation, observation, and reflection. Based on the results of research and discussion it can be concluded as follows. 1) Before applying the Indonesian language learning wall picture media, the material for writing essays did not get a good response from students and student learning mastery was not achieved. 2) After applying the media wall pictures in learning Indonesian, the material for writing essays received good responses from students and student learning completeness achieved very good category scores.